EOCENE VOLCANISM ABOVE A DEPLETED MANTLE SLAB WINDOW IN SOUTHERN ALASKA - Cole R.B.; Nelson S.W.; Layer P.W.; Oswald P.J. (My University, 2006)
The Caribou Creek volcanic field lies along the continent-side edge of forearc basin rocks in south-central Alaska and consists of over 1000 m of shallow-dipping basalt and andesite lavas with minor mafic pyroclastic deposits. Dacite and rhyolite lavas along with shallow intrusions form dome complexes with associated pyroclastic deposits that overlie and crosscut the basalt and intermediate lavas. The basalts are tholeiitic and strongly depleted in the light rare earth elements (La/Yb = 0.18-1.5), with concentrations of high field strength elements (e.g., Zr, Hf, Ti, Y) similar to mid-ocean-ridge basalt and with variable enrichment in fluid-mobile elements (e.g., Cs, Ba, and Ph). Intermediate and felsic rocks show enrichment in the rare earth elements and fluid-mobile elements plus Rb and K, but retain low La/Yb ratios (0.48-3.6). A few andesite and dacite samples are strongly depleted in the heavy rare earth elements and are geochemically similar to adakites (e.g., Sr/Y up to 52). Ten 40Ar/39Ar ages for the Caribou Creek volcanic rocks range from 49.4 ± 2.2 to 35.6 ± 0.2 Ma. An adakite-like tuff beneath the other volcanic rocks yields an age of 59.0 ± 0.4 Ma. Caribou Creek basalts were derived from mid-ocean-ridge-like depleted mantle that was emplaced beneath the southern margin of Alaska through a slab window following spreading ridge subduction. Caribou Creek volcanism was coeval with oblique subduction, oroclinal bending, and right-lateral strike-slip faulting in south-central Alaska, all of which could have induced crustal extension to allow adiabatic melting of the depleted mantle reservoir to form basaltic magmas. The basalts then evolved by fractional crystallization with moderate to high degrees of assimilation of Jurassic arc basement rocks to form the intermediate and felsic magmas. Enrichment of the basaltic parent magmas in fluid-mobile elements occurred by contamination from the Jurassic arc rocks and/or by contamination with metasomatic mantle remnant from preceding subduction. High heat flow through the slab window induced partial melting of garnet-bearing mafic parts of the Jurassic arc basement to form the adakite-like rocks. The Caribou Creek volcanic rocks demonstrate that slab windows can directly influence magmatism inboard of accretionary prism and forearc basin settings given a suitable deformation regime (e.g., crustal extension) and that the influence of a slab window on continental margin magmatism can be long-lived (>20 m.y.). © 2006 Geological Society of America.
Keywords: ADAKITE; ALASKA; EOCENE; SLAB WINDOW; TALKEETNA MOUNTAINS; VOLCANISM; Cenozoic::Paleogene::Eocene; Кайнозой::Палеоген::Эоцен